Academic and industrial tribology research in India—Current status - Sujeet K. Sinha (Friction)
With recent economic developments in India and a large thrust toward green technology and sustainability, tribology research has diversified from industrial maintenance and lubricant-centric tribology a few decades ago to new areas such as nanotribology, bio-tribology, smart coatings, wind turbine gears, and green tribology. In this paper, a brief overview of the current research activities in tribological research in India is presented. The paper is divided into industrial and academic research, and their collaboration status is explored. The industry has continued to work on problems related to the maintenance of bearings, lubrication of machinery, mining equipment, etc., but some new issues are presently being focused on. Some of these examples include problems related to wind turbine gears, hydrogen energy tribology, electric vehicle tribology, ship propellers, nuclear power plant tribology, bio-tribology, and so on. In the academic environment, several new topics are being researched in different university/institute research labs. Bio-tribology and coatings have gained much momentum in academic research, but there is also a sufficient push towards new and environmentally friendly lubricant and grease additives for non-ferrous alloys, etc. This paper will also address some of the issues faced in industrial and academic tribological research arenas in India and how perhaps those issues could be addressed in the near future.